State of pediatric liver transplantation in the United States and achieving zero wait list mortality with ideal outcomes: A statement from the Starzl Network for Excellence in Pediatric Transplant Surgeon's Working Group. (5th December 2022) - Rasmussen, Sara K.; Lemoine, Caroline P.; Superina, Riccardo; Sayed, Blayne; Goldaracena, Nico; Soltys, Kyle A.; Griesemer, Adam; Dick, Andre; Angelis, Michael; Chin, L. Thomas; Florman, Sander; Ganoza, Armando; et al.
Abstract: Background: Liver transplant is a life‐saving therapy that can restore quality life for several pediatric liver diseases. However, it is not available to all children who need one. Expertise in medical and surgical management is heterogeneous, and allocation policies are not optimally serving children. Technical variant grafts from both living and deceased donors are underutilized. Methods: Several national efforts in pediatric liver transplant to improve access to and outcomes from liver transplant for children have been instituted and include adjustments to allocation policies, UNOS‐sponsored collaborative improvement projects, and the emergence of national learning networks to study ongoing challenges in the field the Surgical Working group of the Starzl Network for Excellence in Pediatric Transplantation (SNEPT) discusses key issues and proposes potential solutions to eliminate the persistent wait list mortality that pediatric patients face. Results: A discussion of the factors impacting pediatric patients' access to liver transplant is undertaken, along with a proposal of several measures to ensure equitable access to life‐saving liver transplant. Conclusions: Pediatric liver transplant wait list mortality can and should be eliminated. Several measures, including collaborative efforts among centers, could be leveraged to acheive this goal.